2004
DOI: 10.1074/jbc.m311600200
|View full text |Cite
|
Sign up to set email alerts
|

Differentially Regulated Expression of Endogenous RGS4 and RGS7

Abstract: Regulators of G protein signaling (RGS proteins) constitute a family of newly appreciated components of G protein-mediated signal transduction. With few exceptions, most information available on mammalian RGS proteins was gained by transfection/overexpression or in vitro experiments, with relatively little known about the endogenous counterparts. Transfection studies, typically of tagged RGS proteins, have been conducted to overcome the low natural abundance of endogenous RGS proteins. Because transfection stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(74 citation statements)
references
References 43 publications
2
71
1
Order By: Relevance
“…We focused on the RGS4 gene in view of its association with a number of pathologies and the important role of neurally enriched RGS4 in G protein signaling. Acute increases in RGS4 transcripts in confluent PC6 cells (15) presented an excellent experimental system to elucidate how the RGS4 gene is activated in a neuronal-like cell. First, we identified and cloned the human RGS4 promoter.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We focused on the RGS4 gene in view of its association with a number of pathologies and the important role of neurally enriched RGS4 in G protein signaling. Acute increases in RGS4 transcripts in confluent PC6 cells (15) presented an excellent experimental system to elucidate how the RGS4 gene is activated in a neuronal-like cell. First, we identified and cloned the human RGS4 promoter.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that several RGS genes are induced under certain physiological conditions, for example RGS1 during mitogenic activation of lymphocytes (9), RGS2 in the early stage of 3T3-L1 differentiation to adipocytes (10), RGS16 during genotoxic stress (11), and the yeast RGS gene SST2 by pheromone (12). Regulation of RGS4 expression has also been noted in facial motoneuronal precursors during embryonic development in mice (13), in epithelial and endothelial cells during tubulogenesis (14), and in rat PC12 cells during cell confluence (15). In the study by Grillet et al (13), in situ hybridization was used to demonstrate that RGS4 transcription is increased in differentiating and post-mitotic neurons in the developing mouse nervous system.…”
Section: Regulator Of G Protein Signaling 4 (Rgs4)mentioning
confidence: 99%
See 2 more Smart Citations
“…Western blot analysis was performed as previously described Krumins et al, 2004) using the following primary antibodies: rabbit antiserum against the C terminus of RGS2 (CKKPQITTEPHAT; 1:1000; a generous gift from D. Siderovski, University of North Carolina, Chapel Hill, NC); rabbit antisera against rat RGS4 (Krumins et al, 2004) (1:2000; a generous gift from S. Mumby, University of Texas Southwestern Medical Center, Dallas, TX), affinity purified anti-RGS7 antibodies (Upstate Biotechnologies; 1:10,000), protein A-purified rabbit antibodies made in our laboratory to histagged RGS9c bacterially expressed fragment (He et al, 1998), and SGS rabbit antisera against G␤5 (Zhang et al, 1996) (1:5000; a generous gift from W. Simonds, National Institute of Diabetes and Digestive and Kidney Diseases, Bethesda, MD). The specificities of these RGS and G␤5 antibodies were further confirmed using brain extracts from wild-type (wt) and mutant mice (supplemental Fig.…”
Section: Experimental Parkinsonism and Dyskinesiamentioning
confidence: 99%